Analisis Produktivitas Alat Gali Muat dan Alat Angkut pada Kegiatan Pengangkutan Batubara di PT Lematang Coal Lestari (LCL) - Aditya, Aditya; Yansen , Dedi (Jurnal Inovasi Global, 2025)
The analysis of the productivity of mechanical tools at PT Lematang Coal Lestari (LCL) aims to be an evaluation material for the company for the performance of heavy equipment in the coal transportation process. The results showed an MF value of 0.67 which indicates a work imbalance, where the digging and loading equipment works less than 100% while the transportation equipment works 100%. The productivity of the loading digging equipment reached 310.83 tons/hour with a monthly yield of 139,873.5 tons. Meanwhile, transportation equipment is only 208.40 tons/hour or 93,780 tons/month. The company's production target of 150,000 tons/month has not been achieved because work efficiency is still low, which is 76%. The main obstacles come from the uphill, muddy road conditions and loading patterns that cause waiting times. Efforts to improve the work system are needed to improve work efficiency and achieve production targets.